Algorithmic thinking : a problem-based introduction - Zingaro, Daniel (San Francisco : No Starch Press, 2021)
"An introduction to solving problems with algorithms and data structures, using competitive programming examples. Topics covered include recursion, dynamic programming, graphs, greedy algorithms, heaps, hash tables, segment trees, and other data structures for efficiently handling data"-Provided by publisher"--
Hash tables -- Trees and recursion -- Memoization and dynamic programming -- Graphs and breadth-first search -- Shortest paths in weighted graphs -- Binary search -- Heaps and segment trees -- Union-find.
Includes bibliographical references and index.
CSE
Book Finder International
Keywords: Computer algorithms -- Problems, exercises, etc; Computer programming -- Problems, exercises, etc; Computer science